AN INVESTIGATION OF 21st CENTURY PEDAGOGICAL ELEMENTS AND THE NAQLI-AQLI KNOWLEDGE IN PRE-SERVICE TEACHERS AT SELECTED PUBLIC SECONDARY NATIONAL SCHOOLS - Haliza Harun; Norhaili Massari; Normazla Ahmad Mahir; Noor Saazai Mat Saad; Hazlina Abdullah; Ramiaida Darmi; Siti Rosilawati Ramlan; Sarifah Nurhanum Syed Sahuri, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
21st Century Learning has commonly been directed to optimise learners’ acquisition of knowledge and skills. However, less emphasis is placed on the 21st century skills needed by the teachers, particularly in the teaching of Islamic Religious Studies which emphasises the integration of Naqli and Aqli knowledge. Saavedra and Opfer (2012) propose these nine pedagogical elements of 21stCentury Skills required for the 21stCentury Teaching; Making it relevant, teaching through the disciplines, developing thinking skills, Encouraging learning transfer, Teaching students how to learn, Addressing misunderstandings directly, Treating teamwork like an outcome, Exploiting technology to support learning and Fostering creativity. This paper investigated the knowledge, skills of 21st Century learning and the Naqli-Aqli knowledge that teacher trainees impart in their practicum training. Analysis is based on 21 Reflective Journals written by 21 pre-service teachers during their 4-month Practicum Training in public secondary national schools. Through rich and exclusive data, findings indicate that the teacher trainees to some extent did adopt some of these pedagogical elements as well as the integration of Naqli-Aqli knowledge. It is hoped that this paper is able to reveal some insights in understanding the issues of implementing 21st Century Learning and integrating the Naqli-Aqli knowledge in classrooms.